2004
DOI: 10.1556/avet.52.2004.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococci isolated from animals and food with phenotypically reduced susceptibility to β-lactamase-resistant β-lactam antibiotics

Abstract: The antibiotic resistance pattern of 1921 Staphylococcus strains isolated from animals and food within the last two years were examined using diffusion tests. Among them there were only 35 strains of S. aureus having an inhibition zone diameter of 15 mm or less, and 4 strains of coagulase-negative staphylococci (CNS) having a zone diameter of 18 mm or less to 1-µg oxacillin disk. These 39 strains were examined also by E-test to oxacillin and for the detection of the mecA gene by PCR in order to determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
2
16
0
3
Order By: Relevance
“…There were no significant phenotypic differences observed between isolates from different sources, which mean probably the same potential of pathogenicity. Several reports suggest that the transfer of S. aureus between human and cattle is possible and that the infection of humans by transmission through food products contaminated with animal MRSA is very plausible (Roberson et al, 1994;Zadoks et al, 2000;Lee, 2003;Kaszanyitzky et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no significant phenotypic differences observed between isolates from different sources, which mean probably the same potential of pathogenicity. Several reports suggest that the transfer of S. aureus between human and cattle is possible and that the infection of humans by transmission through food products contaminated with animal MRSA is very plausible (Roberson et al, 1994;Zadoks et al, 2000;Lee, 2003;Kaszanyitzky et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Kaszanyitzky et al (2004), a total of 1005 staphylococcal strains were isolated from carcasses or samples of different animal species and analysis indicated that only 21 were confirmed as methicillin resistant S. aureus (19 originated from cows, 1 poultry and one from horse), six of these harboured the mecA gene. In Hungary, 806 staphylococci from different sources were isolated and only 2% of S. aureus from cattles were resistant to methicillin and were mecA-negative, none of the isolates from pigs and poultry were MRSA (Kaszanyitzky et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most effective antibiotics were enrofloxacin, streptomycin and gentamicin. This high sensitivity was also demonstrated in other studies (Kaszanyitzky et al, 2004;Byarugaba, 2004). Despite these data, Freitas et al (2005) reported high resistance level to gentamicin in CoNS isolated in regions where this antibiotic was used.…”
Section: Discussionmentioning
confidence: 57%
“…Kaszanyitzky et al, 2004). A transmissão desses genes pode envolver tanto espécies patogênicas como membros da microbiota indígena dos hospedeiros.…”
unclassified